0528 Insomnia Symptoms and Adherence to CPAP: Exploring the Role of Resilience. (12th April 2019) - Williams, Natasha J; Butler, Mark; Roseus, Josue; Parra, Yoanna; Krieger, Ana C; Ebben, Matthew; Barnes, Andrea; Wallace, Douglas M; Blanc, Judite; Chung, Alicia; Jean-Louis, Girardin
Abstract: Introduction: Several studies have demonstrated that insomnia symptoms negatively impact adherence to Continuous Positive Airway Pressure (CPAP). Yet, little is known about psychosocial factors that may buffer the associated negative effects. The present study explored the role of resilience, the ability to function in the face of or following adversity, on reducing the negative effects of insomnia on CPAP adherence. Methods: The study sample included volunteers from a large sleep center enrolling individuals newly diagnosed with Obstructive Sleep Apnea (OSA). For this analysis, we examined volunteers with complete data (n=45) on insomnia severity (based on the Insomnia Severity Index (ISI)), resilience (based on the Connor Davidson Resiliency Scale (CD-RISC)), and objective median hours of CPAP use over the first 30 days of treatment. Results: The mean age was 55.4 years (SD=15.7); 62.2% male, and 33% black. The mean ISI score was 13.0 (SD=6.3), mean CD-RISC was 30.7 (SD=5.7) and mean CPA use over the first 30 days was 5.9 (SD=1.9). In the linear regression, ISI was positively correlated with increased hours of CPAP use (r=-0.305, p=.047). Resilience was not significantly correlated with CPAP use (r=0.216, p=.163), likely attributable to the sample size. ISI correlated with CPAP use among those with low resilience (r=-0.461, p=.027), but not among those with high resilience (r=-0.039, p=.870). There was a significant interaction (B(SE)=0.22 (0.08); p=.005) between ISI and resilience on median hours of CPAP use, indicating that resilience may moderate the association between ISI and hours of CPAP use. Conclusion: Results of our study indicated that resilience is an important factor and may reduce the negative effects of insomnia on CPAP adherence. Notably, the high resilience score in this sample could signal an important target for tailoring CPAP adherence interventions to address unique characteristics of each subgroup. Support (If Any): K23HL125939